2016
DOI: 10.1016/j.bbagen.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of αB-crystallin: Role in stress, aging and patho-physiological conditions

Abstract: Phosphorylation of αB-crystallin has dual role that manifests either beneficial or deleterious consequences depending on the extent of phosphorylation and interaction with cytoskeleton. Considering that disease-causing mutants of αB-crystallin are hyperphosphorylated, moderation of phosphorylation may be a useful strategy in disease management. This article is part of a Special Issue entitled Crystallin Biochemistry in Health and Disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 176 publications
0
55
0
Order By: Relevance
“…In inflammatory spinal cord lesions, stellate astrocytes express HSPB5 ser59 prominently, while hypertrophic astrocytes express HSPB5 ser19 and, to a lesser extent, HSPB5 ser45. HSPB5 is involved in a multitude of cellular processes by interacting with more than 90 different proteins, necessitating mechanisms to post‐translationally regulate HSPB5 activity, such as phosphorylation . HSPB5 can be phosphorylated at three different serine residues (ser19, ser45 and ser59).…”
Section: Discussionmentioning
confidence: 99%
“…In inflammatory spinal cord lesions, stellate astrocytes express HSPB5 ser59 prominently, while hypertrophic astrocytes express HSPB5 ser19 and, to a lesser extent, HSPB5 ser45. HSPB5 is involved in a multitude of cellular processes by interacting with more than 90 different proteins, necessitating mechanisms to post‐translationally regulate HSPB5 activity, such as phosphorylation . HSPB5 can be phosphorylated at three different serine residues (ser19, ser45 and ser59).…”
Section: Discussionmentioning
confidence: 99%
“…The second actor, αB‐crystallin, is known to be the molecular chaperone of desmin, playing a role in the localization and aggregation of desmin filaments as well as in its assembly . Activity of αB‐crystallin was first known to be regulated by phosphorylation, while its O‐GlcNAcylation on Thr170 seemed regulate its localization . Recently, the Thr162 residue on αB‐crystallin was identified to be O‐GlcNAcylated as well; this residue is located on its C‐terminal domain known to directly interact with desmin .…”
Section: Emergence Of a New Role Of O‐glcnacylation In The Sarcomere mentioning
confidence: 99%
“…αB-crystallin is a molecular chaperone involved in the cell response to stress in various tissues (see reviews in [51,52]). Loss-of-function studies demonstrated that αB-crystallin is critical in maintaining lens proteostasis [37], and several missense mutations in human αB-crystallin gene are linked to hereditary cataracts, including P20S [53] and D140N [54].…”
Section: Expression Of Murine αB-crystallin R120g Mutant Induces Zebrmentioning
confidence: 99%